An attempt to preserve archival analog seismic records from Geotraverses in Ukraine - Lysynchuk, D.V.; Kolomiyets, K.V.; Stepanenko, V.M. (Geofizicheskiy Zhurnal, 2025)
Between 1960 and 1990, extensive deep seismic studies were conducted in Ukraine, significantly enhancing the understanding of the Earth’s crust and mantle, particularly within the Ukrainian Shield. This paper introduces a methodology for digitizing analog seismic records preserved on photographic paper, representing a crucial step in safeguarding historical data. Test digitization of a section of the Geotraverse IV demonstrated the feasibility of creating vectorized images, enabling the modern interpretation of seismic data. The results confirmed the potential to extract new insights, particularly regarding shear waves, and process them further in the SEG-Y format. Comprehensive scanning and systematic organization of these archives could support the reinterpretation and long-term preservation of valuable scientific data.